ESTADO DE HUMOR E DESEMPENHO: UMA ANÁLISE SOB A ÓTICA DA TEORIA DA CATASTROFE - Leonardo Pestillo de Oliveira; Alissianny Haman Fogagnoli; Lenamar Fiorese Vieira (Universidade Estadual do Oeste do Paraná, 2015)
This study sought to examine the mood and anxiety as factors influencing sports performance of athletes participating in Futsal Finals Youth Games of Parana in 2011. The sample consisted of 11 male athletes from team Campo Mourão, aged between 16 and 18 years. The instruments used to assess the mood was the Brazilian Mood Scale (BRAMS) validated by Rohlfs et al (2006), since anxiety was analyzed using the Competitive State Anxiety Inventory (CSAI-2), which are applied before and after each match. For data analysis was used for qualitative and descriptive statistics. The results allowed to conclude that the change in mood of athletes during the competition can be considered a factor that contributed to the defeat in the semifinal match, and the extent to which anger can be varied more crucial in the perception of athletes and their ability to win, since the same self-confidence also fell throughout the competition. It is concluded that for this team, the size of humor and anger characteristic of self-confidence may have been high points in the defeat of team in a match considered important.